High Fat Diet Attenuates the Anticontractile Activity of Aortic PVAT via a Mechanism Involving AMPK and Reduced Adiponectin Secretion - Almabrouk, Tarek A. M.; White, Anna D.; Ugusman, Azizah B.; Skiba, Dominik S.; Katwan, Omar J.; Alganga, Husam; Guzik, Tomasz J.; Touyz, Rhian M.; Salt, Ian P.; Kennedy, Simon (Frontiers in Physiology, 2018)
Background and aim: Perivascular adipose tissue (PVAT) positively regulates vascular function through production of factors such as adiponectin but this effect is attenuated in obesity. The enzyme AMP-activated protein kinase (AMPK) is present in PVAT and is implicated in mediating the vascular effects of adiponectin. In this study, we investigated the effect of an obesogenic high fat diet (HFD) on aortic PVAT and whether any changes involved AMPK. Methods: Wild type Sv129 (WT) and AMPKα1 knockout (KO) mice aged 8 weeks were fed normal diet (ND) or HFD (42% kcal fat) for 12 weeks. Adiponectin production by PVAT was assessed by ELISA and AMPK expression studied using immunoblotting. Macrophages in PVAT were identified using immunohistochemistry and markers of M1 and M2 macrophage subtypes evaluated using real time-qPCR. Vascular responses were measured in endothelium-denuded aortic rings with or without attached PVAT. Carotid wire injury was performed and PVAT inflammation studied 7 days later. Key results: Aortic PVAT from KO and WT mice was morphologically indistinct but KO PVAT had more infiltrating macrophages. HFD caused an increased infiltration of macrophages in WT mice with increased expression of the M1 macrophage markers Nos2 and Il1b and the M2 marker Chil3. In WT mice, HFD reduced the anticontractile effect of PVAT as well as reducing adiponectin secretion and AMPK phosphorylation. PVAT from KO mice on ND had significantly reduced adiponectin secretion and no anticontractile effect and feeding HFD did not alter this. Wire injury induced macrophage infiltration of PVAT but did not cause further infiltration in KO mice. Conclusions: High-fat diet causes an inflammatory infiltrate, reduced AMPK phosphorylation and attenuates the anticontractile effect of murine aortic PVAT. Mice lacking AMPKα1 phenocopy many of the changes in wild-type aortic PVAT after HFD, suggesting that AMPK may protect the vessel against deleterious changes in response to HFD.